1961
DOI: 10.1136/jcp.14.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of hospital blankets with synthetic phenolic compounds

Abstract: SYNOPSIS A cheap method by which hospital blankets may be effectively disinfected (approximately 3d. per blanket) is described. A recommendation is made that blankets from the patients' beds be divided into: 'socially dirty' blankets to be laundered, possibly at infrequent intervals; and 'socially clean' blankets to be disinfected frequently. The wide range of a synthetic phenolic compound is described. This substance is effective against all the common pathogenic bacteria in the presence of organic matter, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1962
1962
1971
1971

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Pressley' showed by a slit sampling technique that the proportion by number of wool fibres in hospital dust was very small, the proportion of protein fibres (which would include wool) being only 3.2%, the overwhelming majority, 96.2%, being cellulose (which would include cotton and viscose rayon). Similar results have been obtained by Larkin et al 2 Moreover, Rubbo et al3 found that the proportion of protein fibres collected on plates ranged from 20.6% at floor level to 6.9% at a height of 9 ft. (2.7 m.): once again cellulose fibres were predominant, the corresponding figures being 79.4% and 93.1%. Near bed level (3 ft. (0.9 m.)) the proportions were 87.4% cellulose and only 12.6% protein.…”
supporting
confidence: 79%
“…Pressley' showed by a slit sampling technique that the proportion by number of wool fibres in hospital dust was very small, the proportion of protein fibres (which would include wool) being only 3.2%, the overwhelming majority, 96.2%, being cellulose (which would include cotton and viscose rayon). Similar results have been obtained by Larkin et al 2 Moreover, Rubbo et al3 found that the proportion of protein fibres collected on plates ranged from 20.6% at floor level to 6.9% at a height of 9 ft. (2.7 m.): once again cellulose fibres were predominant, the corresponding figures being 79.4% and 93.1%. Near bed level (3 ft. (0.9 m.)) the proportions were 87.4% cellulose and only 12.6% protein.…”
supporting
confidence: 79%
“…Although boiling of blankets on a large scale has been routine practice for several years at hospital laundries in Australia (Cowling, 1959;Standards Association of Australia, 1962), and boiling has the advantage that mycobacteria may be destroyed, it has not yet been universally accepted in other countries. In view of this and the observation that conventional laundering with soap is very ineffective in removing bacteria (Blowers & Wallace, 1955;Frisby, 1957;Ravenholt, Baker, Wysham & Giedt, 1958;Schwabacher, Salsbury & Fincham, 1958; Thomas, Liddell & Carmichael, 1958;Larkin, Bridson, Grieve & Gibson, 1961; Dickinson, Wagg & Carter, 1962) the potentialities of washing with bactericides warrant closer investigation. Bactericides have not proved as effective in laundering trials with new woollen blankets as would be expected from the activities of the bactericides as measured by standard methods; the present paper is concerned with the possibility that this low efficiency of the bactericides may be due to their adsorption by the wool.…”
Section: Introductionmentioning
confidence: 99%